Pengaruh Brand Ambassador BTS Terhadap Minat Beli Warga Taman Duta di E-Commerce Tokopedia (Survey Pada Pengguna Tokopedia di Perumahan Taman Duta) - Fery David; Salman (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Tokopedia is one of the largest E-commerce in Indonesia, which until now has reached the Unicorn stage. Tokopedia also invited Korean boyband BTS to collaborate as its Brand Ambassador. This study aims to determine the effect of BTS Brand Ambassadors on the purchasing interest of Taman Duta residents in Tokopedia E-commerce to Tokopedia users at Taman Duta Housing. This study uses a positivism paradigm with a quantitative approach and survey methods. The data that the researchers obtained were processed using the SPSS Statistics program with a total sample of 116 respondents. The data analysis technique used is the Pearson's Product Moment correlation test, simple linear regression test, the coefficient of determination, and the T test. The theory used in this study is the Stimulus-Response (S-R) theory. The results of the hypothesis analysis state that there is an influence between BTS Brand Ambassador and Purchase Intention. This research resulted in a percentage of 39.8% which was carried out on Tokopedia users who could receive a stimulus to the BTS Brand Ambassador.